2022
DOI: 10.2147/jir.s352250
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Nutritional Risk Index and Handgrip Strength on the Survival of Patients with Cancer Cachexia: A Multi- Center Cohort Study

Abstract: The nutritional risk index (NRI) and handgrip strength (HGS) are useful indicators of nutritional and physical status, respectively, both of them can predict the prognosis of many cancers; however, the predictive accuracy of a single indicator is unsatisfactory. Whether the combination of NRI and HGS could enhance the stratification of the prognosis of patients with cancer cachexia. Patients and Methods:The study population was randomly divided into training and validation cohorts. We combined NRI and HGS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
(31 reference statements)
1
5
1
Order By: Relevance
“…Although HGS was suggested to be an independent prognostic factor in patients with cachexia, 34 its prognostic value in the present study was lower than that of the TA. This finding was similar to a previous study showing that a low fat mass index outperforms handgrip weakness and malnutrition in predicting cancer survival 17 .…”
Section: Discussioncontrasting
confidence: 85%
“…Although HGS was suggested to be an independent prognostic factor in patients with cachexia, 34 its prognostic value in the present study was lower than that of the TA. This finding was similar to a previous study showing that a low fat mass index outperforms handgrip weakness and malnutrition in predicting cancer survival 17 .…”
Section: Discussioncontrasting
confidence: 85%
“…Patients in the high NRI group had a significantly better OS than those in the low NRI group. Consistent with the results of previous studies in other cancers, our results suggest that malnutrition, as assessed by the NRI, may be a predictor of poor survival in patients with NDMM [22][23][24].…”
Section: Discussionsupporting
confidence: 92%
“…But in our study, a linear association was found within the grip strength of 34.2 kg, i.e., among people with lower grip strength. One possible reason may be adults over 45 years old in China suffer from early-childhood malnutrition [ 21 ]. Famine can cause malnutrition and deficiencies in body composition, which constituted an extreme loss of life [ 22 ].…”
Section: Discussionmentioning
confidence: 99%